Isolation of Egg Yolk Granules as Low-Cholesterol Emulsifying Agent in Mayonnaise - Motta-Romero, Hollman (2023)
Egg yolk is an essential ingredient for many food products due to its excellent functional properties such as emulsification. However, the consumers' concern of its cholesterol level has led food industry to seek solutions for its replacement. Utilization of low-fat egg yolk granules as emulsifier can be an alternative strategy. In this study, granules with low cholesterol content were separated from egg yolk by a simple method under easily scalable centrifugal conditions. The egg yolk granules isolated within 0.17 M NaCl solution achieved a 22.5% yield that was similar to that using higher centrifugation speeds and longer time. The yield of egg yolk granules increased from 25% to 32% when the yolk:water ratio was changed from 1:1 to 1:2. Mayonnaise was prepared to evaluate the emulsifying capacity of the egg yolk granules. It was found that egg yolk granules exhibited similar emulsifying activity as that of whole egg yolk, but a better emulsion stabilizing property that is evidenced by the higher viscosity of mayonnaise prepared with the granules. In addition, the viscosities of mayonnaise prepared by spray dried yolk and granules were slightly higher than the liquid counterpart, showing a further improvement by spray drying on the emulsion stabilizing properties. The mechanical spectra of mayonnaise samples by frequency sweep also suggested that granules favored the formation of stronger 3-dimensional arrangements of oil droplets and therefore a more stable emulsion. Results suggest that granules isolated within 0.17 M NaCl solution present best emulsifying properties and can be applied as whole yolk replacer in food emulsions.